On The (Un)importance of Working Memory in Speech-in-Noise Processing for Listeners with Normal Hearing Thresholds - Füllgrabe, Christian; Rosen, Stuart (Frontiers in Psychology, 2016)
With the advent of cognitive hearing science, increased attention has been given to individual differences in cognitive functioning and their explanatory power in accounting for inter-listener variability in the processing of speech in noise (SiN). The psychological construct that has received much interest in recent years is working memory (WM). Empirical evidence indeed confirms the association between WM capacity (WMC) and SiN identification in older hearing-impaired listeners. However, some theoretical models propose that variations in WMC are an important predictor for variations in speech processing abilities in adverse perceptual conditions for all listeners, and this notion has become widely accepted within the field. To assess whether WMC also plays a role when listeners without hearing loss process speech in adverse listening conditions, we surveyed published and unpublished studies in which the Reading-Span test (a widely used measure of WMC) was administered in conjunction with a measure of SiN identification, using sentence material routinely used in audiological and hearing research. A meta-analysis revealed that, for young listeners with audiometrically normal hearing, individual variations in WMC are estimated to account for, on average, less than 2% of the variance in SiN identification scores. This result cautions against the (intuitively appealing) assumption that individual variations in WMC are predictive of SiN identification independently of the age and hearing status of the listener.